Relationship between resilience and social skills in a group of adolescents in northern Lima - Ángeles Donayre, Mariuccia (2017)
The present study’s objective was to determine the relationship between resilience and social skills in a group of teenagers. The sample was composed by 515 students of both sex of 6th grade of primary education in two districts of Lima Norte, whose ages were between 10 and 12 years old. The instruments used were The Personal Factors of Resilience Inventory proposed by Salgado (2005) and The Check List of Social Skills by Goldstein (1978) previously adapted; the type of study is basic-level descriptive correlational, non-experimental design, cross-type. The results showed there is not a significant relationship between resilience and social skills; however, there are significant relationships between the empathy factor and five dimensions of social skills, except the dimension of planning skills, as well as a statistically significant relationship with the global social skills.